Validation of a paediatric thyroid phantom using different multidetector computed tomography models. (March 2016) - Alsabbagh, M; Ng, L Y; Tajuddin, A A; Manap, M A; Zainon, R
Abstract: The aim of this study was to compare the attenuation values of a fabricated paediatric thyroid phantom material using different MDCT models. A paediatric thyroid phantom was designed to mimic the shape and size of a paediatric patient with an age of 9 years using high- density Polyethylene as the phantom material. The fabricated phantom was scanned using two different multidetector CT scanners (16- and 128-row detectors). The CT numbers were evaluated and the mass attenuation coefficients (μ/ρ) of the phantom material were obtained at each applied energy from each scanner. The results were compared with the tables of the National Institute of Standards and Technology (NIST). The CTs of 16- and 128-row detectors showed that the obtained attenuation values are very similar to the NIST's values. However, the CT of the 128-row detectors showed a slightly much closer match to the NIST's values. This refers to the type and quality of the electronic connections between the detectors. Furthermore, the type and number of detectors (16- and 128-detectors) could affect the details and quality of the output images. The results show that different multidetector CTs can be used to validate the phantom and determine the mass attenuation coefficients of its material.